Study on Characterization and Sedimentary Environment of Tidal Sand Ridges - Zhao, Run; Zhang, Ganggui; Wu, Yupeng (Scientific Journal of Technology, 2025)
As an important marine sedimentary geomorphic unit, the spatial distribution characteristics of tidal sand ridges hold significant guiding significance for oil and gas resource exploration and coastal zone management. This study systematically sorts out the morphological characteristics, sedimentary structures, and formation-evolution mechanisms of typical tidal sand ridges at home and abroad. Through comparative analysis, it is found that relevant research mainly focuses on two aspects: the statistical characterization parameters and sedimentary facies division of continental shelf sand ridges, as well as hydrodynamic-sedimentary coupling simulation and 3D geological modeling. Based on the integration of multi-source data, a multi-dimensional characterization system is proposed, which includes morphological parameters (aspect ratio, slope aspect angle), sedimentary sequences (grain size rhythm, ichnofossil assemblage), and hydrodynamic responses (tidal current rose diagram, vortex intensity). The applicability of this system is verified by previous comparative studies on tidal sand ridges in the offshore area of the Yangtze River Estuary and the North Sea.